Pharmacogenomics – how close/far are we to practising individualized medicine for children? - Sing, Chor-Wing (Br J Clin Pharmacol, 2015)
The translation of pharmacogenomics into clinical practice is a key approach for practising individualized medicine, which aims to maximize drug efficacy and minimize drug toxicity. Since the completion of both the Human Genome Project and the International HapMap project, the development of pharmacogenomics has been greatly facilitated. However, progress in translating pharmacogenomics into clinical practice, especially in paediatric medicine, is unexpectedly slow. Many challenges from different areas remain. This paper discusses the existing applications and the limitations to the implementation of paediatric pharmacogenomics, as well as possible solutions for overcoming these limitations and challenges.